Preparation of BSA-ZnWO4 Nanocomposites with Enhanced Adsorptional Photocatalytic Activity for Methylene Blue Degradation - Pardeep Singh; Pankaj Raizada; Deepak Pathania; Amit Kumar; Pankaj Thakur (International Journal of Photoenergy)
This study explains the effect of adsorption on dye degradation using bovine serum alum and ZnWO4 based nanocomposite (BSA-ZnWO4). The synthesis of BSA-ZnWO4 was performed by a hydrothermal method involving the encapsulation of ZnWO4 with BSA. BSA-ZnWO4 was characterized by SEM, TEM, XRD, FTIR, and UV-Vis spectral techniques. The photocatalytic experiments were performed under solar light. The dye removal was investigated under different reaction conditions. The photocatalytic efficiency of solar/BSA-ZnWO4 process was higher compared to solar/ZnWO4, dark/BSA-ZnWO4, solar/BSA, dark/ZnWO4, and solar light systems. The simultaneous adsorption and photodegradation process (A + P) was the most efficient process due to rapid destruction of adsorbed dye molecules. BSA-ZnWO4 showed superior degradation efficiency and reusability over ZnWO4 for MB degradation.